Schnitzler's Disease as an Important Differential Diagnosis of Chronic Recurrent Multifocal Osteomyelitis: A Case Report. (5th August 2012) - Schrödl, Kathrin; Nigg, Axel; Treitl, Marcus; Flaig, Michael; Jansson, Annette; Schulze-Koops, Hendrik; Reindl, Christiane
Abstract : Introduction . At first sight, chronic recurrent multifocal osteomyelitis (CRMO) and Schnitzler's disease are diagnoses of exclusion and can be similar in their manifestation. Methods . In this paper we present the reevaluation of the 13-year-old diagnosis of chronic recurrent osteomyelitis of a 58-year-old man with chronic ostealgia, night sweat, and pruritic urticarial lesions on the extremities and trunk. For further examination, we performed blood analysis, bone and skin biopsies, CT scans, and magnetic resonance imaging. Results . Laboratory findings showed increased inflammation parameters. Magnetic resonance imaging (MRI) revealed a diffuse bone marrow infiltration. A bone and skin biopsy showed a sclerotic bone marrow involvement and a superficial dermal and perivascular infiltrate of neutrophils. Based on these findings, the diagnosis of Schnitzler's disease was made. Conclusion . Here, we want to present Schnitzler's disease as an important differential diagnosis to CRMO in adults presenting with signs suggestive of CRMO.